Phenotype versus genotype to optimize cancer dosing in the clinical setting-focus on 5‐fluorouracil and tyrosine kinase inhibitors - Jennifer H. Martin; Peter Galettis; Alex Flynn; Jennifer Schneider (Wiley, 2024)
Abstract Cancer medicines often have narrow therapeutic windows; toxicity can be severe and sometimes fatal, but inadequate dose intensity reduces efficacy and survival. Determining the optimal dose for each patient is difficult, with body‐surface area used most commonly for chemotherapy and flat dosing for tyrosine kinase inhibitors, despite accumulating evidence of a wide range of exposures in individual patients with many receiving a suboptimal dose with these strategies. Therapeutic drug monitoring (measuring the drug concentration in a biological fluid, usually plasma) (TDM) is an accepted and well validated method to guide dose adjustments for individual patients to improve this. However, implementing TDM in routine care has been difficult outside a research context. The development of genotyping of various proteins involved in drug elimination and activity has gained prominence, with several but not all Guideline groups recommending dose reductions for particular variant genotypes. However, there is increasing concern that dosing recommendations are based on limited data sets and may lead to unnecessary underdosing and increased cancer mortality. This Review discusses the evidence surrounding genotyping and TDM to guide decisions around best practice.